Guyana Teachers : SABER Country Report 2012 - World Bank Group (World Bank, Washington, DC, 2016)
A new tool, SABER-teachers, aims to help fill this gap by collecting, analyzing, synthesizing, and disseminating comprehensive information on teacher policies in primary and secondary education systems around the world. SABER-Teachers is a core component of SABER (Systems Approach for Better Education Results), an initiative launched by the Human Development Network of the World Bank. SABER collects information about different education systems’ policy domains, analyzes it to identify common challenges and promising solutions, and makes it widely available to inform countries’ decisions on where and how to invest in order to improve education quality. SABER-Teachers collects data on ten core teacher policy areas to offer a comprehensive descriptive overview of the teacher policies that are in place in each participating education system. Data are collected in each participating education system by a specialized consultant using a questionnaire that ensures comparability of information across different education systems. Data collection focuses on the rules and regulations governing teacher management systems. This information is compiled in a comparative database where interested stakeholders can access detailed information organized along relevant categories that describe how different education systems manage their teacher force, as well as copies of supporting documents.